Pengembangan E-Modul Interaktif melalui Educaplay Materi Plantae di SMAN 1 Pulang Pisau - Fahrina, Ririn; Rahmi, Ennike Gusti; Purnaningsih, Titin; Purba, Putri Lidia (Perspektif Pendidikan dan Keguruan, 2026)
Education in the digital age continues to evolve by utilizing technology to create interactive and engaging learning experiences. One of the innovations used is gamification, which is the application of game elements in the learning process. Through the Educaplay platform, interactive multimedia-based E-Modules have been developed that are able to accommodate various learning styles and increase student engagement. In Biology education, particularly in the Plantae (Plants) subject, Educaplay provides activities such as quizzes, puzzles, and educational games that help reinforce conceptual understanding. This study aims to: (1) Determine the structure, (2) Feasibility, (3) Practicality. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). At this stage, we have only reached stage 3, Development. The results of the study show that the interactive E-Module developed is valid and feasible for use, with a rating of 81.17% from subject matter experts, 90.00% from media experts, and 82.00% from language experts. The practicality rating from teachers was 86.84% (very practical) and from students was 83.91% (practical). Thus, this module is feasible and very practical for use in biology learning.